Phylogenetically related soil actinomycetes distinguish isolation sites by their metabolic activities - Kopecky, Jan; Kamenik, Zdenek; Omelka, Marek; Novotna, Jitka; Stefani, Tommaso; Sagova-Mareckova, Marketa (FEMS microbiology ecology, 2023)
Soil environments are inhabited by microorganisms adapted to its diversified microhabitats. The metabolic activity of individual strains/populations reflects resources available at a particular spot, quality of which may not comply with broad soil characteristics. To explore the potential of individual strains to adapt to particular micro-niches of carbon sources, a set of 331 Actinomycetia strains were collected at ten sites differing in vegetation, soil pH, organic matter content and quality. The strains were isolated on the same complex medium with neutral pH and their metabolites analyzed by UHPLC and LC-MS/MS in spent cultivation medium (metabolic profiles). For all strains, their metabolic profiles correlated with soil pH and organic matter content of the original sites. In comparison, strains phylogeny based on either 16S rRNA or the beta-subunit of DNA-dependent RNA polymerase (rpoB) genes was partially correlated with soil organic matter content but not soil pH at the sites. Antimicrobial activities of strains against Kocuria rhizophila, Escherichia coli, and Saccharomyces cerevisiae were both site- and phylogeny-dependent. The precise adaptation of metabolic profiles to overall sites characteristics was further supported by the production of locally specific bioactive metabolites and suggested that carbon resources represent a significant selection pressure connected to specific antibiotic activities.
Keywords: Soil Microbiology; RNA, Ribosomal, 16S; uhlík; metabolic differentiation; soil pH; antibiotic; Streptomyces; organic matter; phylogenetic differentiation; půda; Actinobacteria; micro-niche; Carbon; RNA ribozomální 16S; půdní mikrobiologie; Tandem Mass Spectrometry; fylogeneze; chromatografie kapalinová; Actinomyces; tandemová hmotnostní spektrometrie; Chromatography, Liquid; Phylogeny; Soil